Effects of slightly acidic electrolyzed water on the microbial quality and shelf life extension of beef during refrigeration - Sheng, Xiaowei (Food Sci Nutr, 2018)
Studies on slightly acidic electrolyzed water (SAEW) for decontamination and shelf life extension of beef are limited. This study aimed to evaluate the effects of SAEW and tea polyphenols (Tpp) on the microbiological, physicochemical, and sensory qualities of fresh beef during storage. The changes in total viable count, thiobarbituric acid content, pH, total volatile basic nitrogen, and sensory scores revealed that the required quality standard of the beef treated with distilled water, Tpp, and SAEW was maintained for up to 6–8, 12–14, and 14–16 days, respectively. These results demonstrated that SAEW could effectively extend the shelf life of beef in comparison with that of other treatments. However, there were no significant differences (p > 0.05) between the untreated and SAEW‐treated group in the content of thiobarbituric acid, suggesting that SAEW does not possess antioxidant activity. Therefore, further studies are required to increase its antioxidant activity. This study suggests that SAEW treatment is an effective and promising method to prolong the shelf life of beef by around 8 days at 4°C.